SYNTHESIS AND EVALUATION OF NOVEL PHENACYL BASED CARBOXAMIDE DERIVATIVES OF PIPERIDINE AS ANTIHYPERTENSIVE AGENTS - Akhtaro, Shamim; Saify, Z S; Arif, M; Mushtaq, Nousheen; Dar, Ahsana; Ahmed, Ashfaq (Pakistan Journal of Physiology, 2018)
Background: The research in the field of piperidine has generally been related to the synthesis of useful medicinal drugs. In view of the pharmacological and medicinal importance of piperidine derivatives in different disciplines of medicines the present study has been carried out. Methods: A series of newly synthesized N-substituted phenacyl piperidine derivatives (II-VII and XIII-XIV) has been evaluated for hypotensive activity in normotensive anesthetized rats at the doses of 0.5Î¼g/kg taking acetylcholine and noradrenaline (1Î¼g/kg) as control. Mean arterial blood pressure and heart rate were compared to its respective control values obtained immediately before the administration of test compounds and expressed as percent change. Results: The compounds II, III and XIV showed mild hypertensive activity while compound V, VII and XIII were found inactive at that dose level. However, compound IV showed more hypotensive effect than the starting molecule (I). None of these derivatives affected the heart rate at the same dose. It was also revealed that the carboxamide group has no considerable effects on arterial blood pressure and playing no important role in the increase or decrease of blood pressure.